Factors associated with global cognitive impairment in epilepsy patients: a cross-sectional study in Mataram, Indonesia (Faculty of Medicine Universitas Indonesia, 2022)
BACKGROUND Cognitive impairment is a major complication of epilepsy. This study aimed to investigate the factors associated with the prevalence of cognitive impairment in patients with epilepsy in Mataram, Indonesia. METHODS This cross-sectional study involved 155 consecutive outpatients with epilepsy at Mataram General Hospital, Mutiara Sukma Mental Hospital, and Siti Hajar Hospital, Mataram, Indonesia between September 2017 and August 2020. Data on the patient’s demographic characteristics, epilepsy, treatment variables, and global cognitive status were collected. The association between the determinants of epilepsy-associated cognitive impairment and the prevalence of epilepsy-associated global cognitive impairment was analyzed using logistic regression. RESULTS The prevalence of epilepsy-associated global cognitive impairment was 83.9% and related to a low level of education (odds ratio [OR] = 5.24, 95% confidence interval [CI] = 1.93–14.20), early age at onset (OR = 7.85, 95% CI = 0.82–33.79), and long duration of epilepsy (OR = 8.47, 95% CI = 1.95–36.88). CONCLUSIONS A high prevalence of epilepsy-associated global cognitive impairment was observed in Mataram and was associated with a low level of education, early age at onset, and long duration of epilepsy.